Hydrogen sulfide repairs testicular damage induced by heat stress in rats - Xinyu Guo; Yupeng Yin; Susu Guo; Xiaoyan Chen; Suyan Xie; Shiqin Chen; Yan Huang (FEBS Open Bio)
Heat stress can cause testicular damage and affect male fertility. The gasotransmitter hydrogen sulfide (H2S) is involved in various physiological and pathophysiological processes, with antioxidant and anti‐inflammation effects. The aim of this study was to investigate whether H2S could reduce the testicular damage caused by heat stress. In this study, we constructed a rat heat‐stress model and treated it with H2S. Histopathology, high‐throughput sequencing, bioinformatics analysis and molecular biology methods were used to investigate whether H2S donor NaHS could alleviate heat stress‐induced testicular injury and to explore the underlying mode of action of H2S. Heat stress reduced testis index, sperm quality, sex hormone levels and disturbed testicular structures. High‐throughput transcriptome sequencing and Gene Ontology (GO) enrichment analyses showed that genes involved in inflammation were upregulated in the heat stress group compared to the control group. H2S treatment increased testis index, sperm quality and attenuated pathological alternation and hormone disorder in rats exposed to heat stress. Furthermore, H2S administration reversed increased inflammatory factors tumor necrosis factor‐α, interleukin‐1β and interleukin‐6, and resulted in a significant decrease in malondialdehyde levels and in increased activity of catalase and ratio of reduced/oxidized glutathione compared to the heat stress group. This study suggests that H2S donor NaHS can effectively restore testicular damage caused by heat stress in rats by inhibiting inflammation and oxidative stress.